Practicing gnosis : ritual, magic, theurgy and liturgy in Nag Hammadi, Manichaean and other ancient literature : essays in honor of Birger A. Pearson - De Conick, April D.; Shaw, Gregory, 1951-; Turner, John Douglas (Leiden ; Boston : Brill, 2013)
"Ritual, magic, liturgy, and theurgy were central features of Gnosticism, and yet Gnostic practices remain understudied. This anthology is meant to fill in this gap and address more fully what the ancient Gnostics were doing. While previously we have studied the Gnostics as intellectuals in pursuit of metaphysical knowledge, the essays in this book attempt to understand the Gnostics as ecstatics striving after religious experience, as prophets seeking revelation, as mystics questing after the ultimate God, as healers attempting to care for the sick and diseased. These essays demonstrate that the Gnostics were not necessarily trendy intellectuals seeking epistomological certainities. They were after religious experiences that relied on practices. The book is organized comparatively in a history-of-religions approach with sections devoted to Initiatory, Recurrent, Therapeutic, Ecstatic, and Philosophic Practices. This book celebrates the brilliant career of Birger A. Pearson."--Provided by the publisher.
Section 5. Philosophic practices. The Platonizing Sethian gnostic Interpretation of Plato's Sophist / Zeke Mazur -- Did Plotinus' "friends" still go to church? : communal rituals and ascent apocalypses / Michael Williams -- The meaning of "one" : plurality and unity in Plotinus and later Neoplatonism / Kevin Corrigan -- Theurgy and the Platonist's luminous body / Gregory Shaw.
Includes bibliographical references and index.
Master record variable field(s) change: 650
Keywords: Gnosticism -- History; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Comparative Religion; Gnosticism; Electronic books; History